Plan de negocios para la implementación de un centro turístico y recreacional en el cantón Valencia - año 2021 - Hidalgo Arana, Dayse Elizabeth (2021)
This written report, entitled, Creation of a tourist recreation center in the canton of Valencia during the year 2021, aims to create a business plan for the creation of a recreational site, for which a bibliographic research is used. documentary, descriptive, supported by field research, the methods to be used for information management are the inductive-deductive, as well as the analytical method. The population under study was made up of the population of the canton of Valencia, which may be future potential customers, to whom, through a simple random sampling, the significant sample of 271 people is chosen to whom the survey is applied to obtain information about the acceptance of the site. Among the main results obtained, the population believes that there should be a tourist center in the Canton of Valencia, since there is no place for family recreation and if this place exists, most of the people indicated that they would always visit this tourist center, With this information, the creation of the tourist center is made possible in this place where nature mixes with the fresh waters of the river and the tranquility of the sector for recreation. The work concludes that the creation of the tourist center in the canton of Valencia has a good acceptance by the citizens of the canton and tourists not only from other cities but also foreigners, on the other hand it recommends that tourism ventures be increased, by facilitating financing to the population interested in investing in this undertaking, in order to contribute to the socioeconomic development of the canton.